Diagnosis and Management Options for Achalasia - Fajar Dirgantara Edward; Ade Asyari (Jurnal Otorinolaringologi Kepala dan Leher Indonesia, 2026)
Diagnosis and Management Options for Achalasia Background: Achalasia is a rare esophageal motility disorder characterized by increased lower esophageal sphincter tone and loss of esophageal peristalsis. The main symptoms include difficulty swallowing, vomiting, chest pain, weight loss, heartburn, and respiratory complications due to regurgitation. Objective: To know and understand the diagnosis and management options for achalasia.  Literature Review: All treatment methods aim to reduce outflow resistance and improve dysphagia. It is widely recognized that medical management without endoscopic or surgical intervention plays a minor role in the treatment of achalasia. Standard endoscopic methods include pneumatic dilation, botulinum toxin injection, and, more recently, the increasing availability and acceptance of peroral endoscopic myotomy. Time-tested surgical therapies include Heller myotomy with or without anti-reflux procedures, as well as esophagectomy for advanced-stage achalasia or failure of other surgical methods. Conclusion: Achalasia is a chronic and progressive esophageal motility disorder characterized by failure of lower esophageal sphincter relaxation and loss of esophageal peristalsis. Available management methods include pharmacological and non-pharmacological therapy or surgery, with each intervention selected based on indications and carrying its own side effects and complications.